Evaluation of nutritional characteristics of processed foods and beverages advertised in television in Peru, 2021 - Acosta-Concha-fernández, Lucía (2023)
The objective was to describe the characteristics and nutritional profile of processed foods and beverages advertised during child protection hours (6 am to 10 pm, according to Peruvian regulations) on the two channels with the largest audience on Peruvian television. In this cross-sectional study, 448 hours of television content on 14 random days from 6:00 am to 10:00 pm between January and February 2021 were recorded and 2061 advertisements for processed foods and beverages were identified. The time frame with the most publicity for these foods was between 2:00 pm. and 6:00 pm. (33,9%). The most advertised categories were beverages (41,7%) and confectionery (17,8%). 46,9% of foods exceeded at least one of the technical parameters evaluated in the first stage of the Peruvian law (total sugar, saturated fat, or sodium) and 88,4% would do so in the second stage. The majority of advertised foods and beverages were processed, and most of these exceed critical nutrient parameters.